Are Universities Preparing Students for the 21st Century? A Survey on Students’ Perceptions and Readiness (Journal of Asian Development Studies, 2025)
In the 21st century, universities are expected to equip students with essential skills such as critical thinking, problem-solving, digital literacy, creativity, and collaboration to prepare them for the rapidly evolving job market. This quantitative study investigates students’ perceptions regarding the absence of these competencies in higher education curricula and pedagogies. A structured survey was administered to 300 undergraduate students from six disciplines at Benazir Bhutto Shaheed University Layari, and data were analyzed using SPSS. The results indicate a strong agreement among students that universities do not adequately emphasize experiential learning, interdisciplinary approaches, or real-world applications. The findings highlight the need for curriculum reforms, faculty development programs, and modern pedagogical strategies to align university education with 21st-century demands. The study contributes to the discourse on higher education reform, emphasizing the importance of innovative teaching methodologies, digital integration, and skill-based learning to enhance student readiness for future careers. Future research should explore effective interventions and policy measures to address these gaps.